Analysis of the degradation condition of secondary schools. Case study: Pavilions and prefabricated buildings - Barrelas, Joana; De Brito, Jorge; Correia, João Ramôa (Journal of Civil Engineering and Management, 2016)
This paper presents the analysis of the degradation condition of secondary schools built between 1970 and 1990, in Portugal. The analysis is based on 15 case studies, mainly composed of several independent pavilions and typologically defined as “pavilion schools”. The analysis of the data on the constructive defects, identified in detailed surveys of the case studies and registered in technical reports, involves the implementation of a suitable methodology. The methodology is based on the creation of a database where the contents of the survey reports can be gathered and organized. The system allows obtaining statistical results on the degradation condition of the case studies. The statistical analysis shows that the pathological condition of the buildings is a matter of great concern, considering the significant number of defects diagnosed. The highest level of severity mainly concerns defects on the buildings envelope, where concrete elements are the most affected ones. The degradation conditions of the case studies are mostly a consequence of the poor construction quality resulting from decisions made during design and construction. The economic constraints and the tight schedule concerning the expansion of secondary school facilities are also essential to understand the pathological condition of the buildings. The study presented in this paper contributes to the evolution of the methods and systems developed to support buildings’ rehabilitation. The study presents innovative features related to the typology of the case studies (large secondary schools) and to the buildings’ degradation condition.